Lost Among the Cannibals: Keystone's Misrepresentation of a Nguni Musician (International Journal on Stereo & Immersive Media, 2025)
“Lost Among the Cannibals: Keystone’s Misrepresentation of a Nguni Musician” demonstrates that the Keystone View Company deliberately mislabeled and printed a misleading legend for a stereograph in their 1936 Tour of the World. This stereograph, The Finery of a Native Hunter in the Belgian Congo, is a portrait of a Nguni man, likely Swazi, from South Africa, photographed in 1931 by George K. Lewis for the company. This paper establishes a correct attribution for the portrait through the musical bow that the subject holds, his beadwork, dress, documents of Lewis’ presence in KwaZulu-Natal and Eswatini, and two sister views of the subject. Employing hybridity theory from Homi K. Bhabha, the paper demonstrates that the Keystone company in its deliberate mistitling and racialized characterizing performed a colonialist act of disavowal, which the portrait counters. The stereograph provides a hybrid subject for the viewer that challenges the imperialist program of the Keystone company in its Tour of the World series.